PLANNING PERANCANGAN SISTEM INFORMASI MONITORING LAPORAN KEGIATAN HARIAN BERBASIS PWA PADA KANTOR BUPATI KABUPATEN BANTAENG: PERANCANGAN SISTEM INFORMASI MONITORING LAPORAN KEGIATAN HARIAN BERBASIS PWA PADA KANTOR BUPATI KABUPATEN BANTAENG - Ismi, Nur; Erfina,; Ibrahim, Firmansyah (Jurnal INSYPRO (Information System and Processing), 2024)
Utilization of information technology by government institutions also using a monitoring system known as E-Government is an important part of government sustainability. The obstacle faced by each section head is during the process of making monthly reports, where when making monthly reports activities are often not recorded in the agenda book. To overcome this problem, we need a system that can record the daily activities of each section head systematically and accurately. The system that can solve the above problems is a website system, Progressive Web Apps (PWA) is a concept for implementing website creation that applies technology by building applications using the PWA concept which will make web applications run on various platforms such as websites, desktops, and mobile or Android platforms. Based on the percentage value of the question indicators, the System Usability Scale test results were 80.1 and received a "Good" score in the Adjective rating section and received a grade of "B". The method used by the author for this system design research, the Agile Method is a methodology in software development that is based on an iterative work process consisting of agreed rules and solutions.